Avaliação da postura ortostática em mulheres submetidas ao tratamento cirúrgico da câncer de mama - Milena Martins Lopes (2016)
Breast cancer is the most common cause of cancer death in women and the most common cancer diagnosis in women. Survival past 40 years of women who are diagnosed with breast cancer is increasing in developed countries currently being 85% in five years, while in developing countries these values remain between 50% and 60%. The treatment of breast cancer consists of surgery and the use of adjuvant and neoadjuvant techniques. Surgical treatment causes physical and functional changes in patients with postural changes of the observed physical changes. The objective of this study was to detect and quantify through a quantitative diagnostic feature postural changes resulting from breast cancer surgery in women. Participated in this study five women with documented diagnosis of breast cancer and who underwent modified radical mastectomy surgery and quadrantectomy. The postural evaluation was performed using computerized photogrammetry by the use of SAPO software. Statistical analysis was performed with SPSS software (Statistical Package for the Social Sciences), and for evaluation of changes observed in the pre- and post-surgical phase, we used the nonparametric Wilcoxon test. Postural changes were observed trunk tilt to the side of surgery, changes in the alignment of the spine, increased thoracic kyphosis, pelvic tilt, posterior displacement of the lower limbs and displacement of the trunk forward. We conclude that the surgeries for breast cancer treatment cause postural changes that change over time. The physiotherapy intervention must be made from pre-operative phase to postural problems are identified a priori and thus the treatment is appropriate to the patient. The longitudinal follow-up of these patients without physical therapy intervention, shows that the body is able to adjust attempting a rebalancing of body structures. Meanwhile, a second step of this work would be to check how much physical therapy help to optimize these readjustments. The use of specialized software to quantify such changes was to this work, a very important, valid and reliable tool. Despite the limitations found in relation to its clinical use, it is noteworthy that its improvement is a valid and desired clinical justification.